(untitled) (Patan Prospective Journal, 2023)
Tribhuvan University (TU) is the only central and the eldest university in Nepal. It has been the role model of the other universities here and it has own identity globally in the meaning of number of student, provision of various subjects, eco-friendly landscape with the sufficient physical infrastructure and so on. It is still the prime choice of Nepali students whose economy is poor for higher studies, but those who are financially sound, try to go abroad after school level education. Despite TU having enough land property including human resources in comparison to other Nepali universities, the students do not seem fully satisfied in average with the academic activities, some central level educational policies, management system, service and hospitality of the core staffs resultantly unable to perform excellent in the final examination. Keeping old and new some philosophies of education in the mind, for example, Socrates, John Dewey, E. George Payne and some others, this research article renders passionately in the mind of many stakes holder student and teachers at TU’s one constituent campus, Patan Multiple Campus, Patandhoka (Lalitpur) as a sample study through interviews. It reads some lines of the Nepali mass media in the recent so that the related authorities of TU will get feedback for rectification in time in the favor of the nation as well as to reset its own glorious past image in the society, thus, quasi-experimental method works in this article.